A Comparison of Transvaginal Removal and Repair of Uterine Defect for Type II Cesarean Scar Pregnancy and Uterine Artery Embolization Combined With Curettage - Cao, Shanshan; Qiu, Guijing; Zhang, Peipei; Wang, Xinyan; Wu, Qing (Frontiers in Medicine, 2021)
Background: To evaluate the efficacy, safety and cost of transvaginal removal and repair (TRR) of uterine defect for type II Cesarean Scar Pregnancy (CSP II) and compare to Uterine Artery Embolization (UAE) and Curettage. Methods: This was a retrospective study included 87 patients diagnosed with CSP II and treated by UAE combined with curettage and hysteroscopy (n =53) or TRR (n =34) . Clinical data and outcome were analyzed. Results: Two groups showed the similar success rates. TRR group, compared with UAE group had significantly lower complication rates (30.19% vs 8.82%, P< 0.05), lower total costs (13765.89±2029.12 vs 9063.82±954.67, P< 0.05). After the TRR, the anterior lower uterine segment myometrium were thicker, no patients suffered from recurrent CSP. 88.24% (30/34) patients of TRR group have a full term delivery without uterine rupture. Conclusions: Transvaginal resection of the gestational mass and wound repairment is a safe and effective treatment for CSP II with high cost-effective result, especially for the patient with future fertility desire.